2007
DOI: 10.3168/jds.s0022-0302(07)71643-0
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Welfare of Dairy Cows in an Alternative Housing System in Minnesota

Abstract: The compost bedded pack dairy barn is an alternative housing system for lactating cows that has received increased attention in the last 2 yr. No descriptive data were available about this housing system. Therefore, a study of 12 compost dairy barns in Minnesota was conducted between late June 2005 and September 2005. The objectives of this study were to describe the housing system, identify management practices used in these herds, observe cow welfare, analyze herd performance and udder health prior to and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
160
4
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(185 citation statements)
references
References 20 publications
13
160
4
8
Order By: Relevance
“…Alternatives to cubicle accommodation for dairy cattle are emerging (Barberg et al, 2007;Gazzola et al, 2007;O'Driscoll et al, 2008). A potentially viable system consists of group housing cows on an organic bedding substrate without physical constructions such as cubicles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatives to cubicle accommodation for dairy cattle are emerging (Barberg et al, 2007;Gazzola et al, 2007;O'Driscoll et al, 2008). A potentially viable system consists of group housing cows on an organic bedding substrate without physical constructions such as cubicles.…”
Section: Introductionmentioning
confidence: 99%
“…A potentially viable system consists of group housing cows on an organic bedding substrate without physical constructions such as cubicles. One example of this is a bedded pack system, which is of growing interest to dairy producers in the US (Barberg et al, 2007). However, Barberg et al (2007) reported that excellent cow preparation for milking procedures and management of the pack were necessary to achieve low bulk tank SCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have already been successfully built and operated for quite some time in Israel and America. A lot of the scientific findings currently available on this kind of housing system come from America, especially Minnesota [1]- [5].…”
Section: Introductionmentioning
confidence: 99%
“…In vrijloopstallen worden over het algemeen de volgende bacterietypen gevonden met hun frequentie van voorkomen: coliform-achtige bacteriën (10,7%), omgevingsstreptococcen (39,4%), omgevingsstaphylococcen (17,4%) en Bacillus (32,5%) (Barberg et al, 2007a). Coliforms zijn o.a.…”
Section: Economische Vergelijking Van Staltypen In Nederlandunclassified